Mushash 163, Jordanien. Die Grabungskampagnen 2017 - Bartl, Karin (e-Forschungsberichte des DAI, 2017)
The early Neolithic site of Mushash 163 is one of the few known settlements of the Late Pre-Pottery Neolithic A/PPNA (9800–8800/8700 calBC) and Early Pre-Pottery Neolithic B/EPPNB (8700/8600–8300/8200 calBC). A geophysical survey carried out in 2013 showed a settlement size of about 45 × 65 m with a large number of round houses. During five short field seasons on the years 2014–2017, where multiple soundings were conducted, which confirmed the geophysical data and led to a variety of new information for the 9th millennium BC determined.